The economics of MOOCs: a sustainable future?. Issue 1 (6th July 2015) - Porter, Sarah
Abstract : Purpose: – The purpose of this paper is to describe the present interest in the current and predicted business models of Massive Open Online Courses (MOOC); the business models that are being used by MOOC platforms and MOOC providers; discussion of the key issues and challenges; predictions about the future MOOC business models from the perspectives of platforms, providers and consumers. Design/methodology/approach: – Review of the current literature for business models and costs for MOOCs and including the business models of higher education and possible future of the higher education system. Findings: – The findings of this paper show that most MOOCs are currently based upon a "freemium" model where content is provided freely and additional services are charged for; that there are already a range of different "flavours" of MOOC and that this range is likely to further develop over time with some clear winners emerging; and that completely free and open MOOCs are not likely to be the focus of growth in the future, rather MOOCs that are sustained through charges to customers. Practical implications: – To inform the debate about likely future business models and to help greater understanding of possible business models for MOOCs to inform decision-making by managers at universities. Originality/value: – To inform the debate about likely future business models and to help greater understanding of possible business models for MOOCs to inform decision-making by managers at universities.